Scoliosis, life style and low back pain in adolescents - Jandrić, Slavica Dj.; Kragulj, Predrag (Vojnosanitetski pregled, 2021)
Background/Aim. Various internal and external factors could have an influence on the appearance of scoliosis and other postural disturbances in adolescents. The aim of this study was to investigate the correlation between scoliosis and other postural disturbances, physical activity, nutritional habits, as well as its association with comorbidities and age. Methods. This cross-sectional study involved 212 adolescents with the average age of 12.74 ± 1.34 years that were selected by a random selection of attended class of elementary school. A modified “The Physical Activity and Postural Disturbance Test” was used for the study. For statistical analysis Pearson’s test of correlation and linear regression were used to estimate the association between scoliosis and postural disturbances, age, and physical activity, nutritional habits and comorbidities in adolescents. Results. It was shown that there was a statistically significant association between scoliosis and age (r = 0.228, p < 0.05), a significant negative correlation with lordosis (r = -0.207, p < 0.05) and a statistically significant positive correlation between scoliosis and flatfoot (r = 0.279, p < 0.01), metatarsus varus (r = 0, 2, p < 0.05) and low back pain (r = 0.304, p < 0.05). The results of linear regression with the scoliosis, as a dependent variable, and low back pain and other diseases as independent variables have shown that low back pain was significantly associated with scoliosis (p < 0.05). Conclusion. Scoliosis in adolescents is significantly associated with age and postural disturbances, especially with foot postural disturbances, as well as with low back pain.